Martensite decomposition in Cu-Al-Mn-Ag alloys - Andrade dos Santos, Camila Maria [UNESP]; Adorno, Antonio Tallarico [UNESP]; Galdino da Silva, Ricardo Alexandre; Carvalho, Thaisa Mary [UNESP] (Elsevier B.V., 2014)
The influence of Mn and Ag additions on the isothermal kinetics of martensite decomposition in the Cu-9wt.%Al alloy was studied using X-ray diffractometry (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDXS) and microhardness changes measurements with temperature and time. The results indicated that the reaction is disturbed by the increase of Mn, an effect associated with the increase in the Al-Mn and Cu-Mn atomic pairs, which disturbs Cu diffusion and increases the activation energy for the martensite decomposition reaction. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Metals and alloys; Solid state reactions; Kinetics